Exercise intensity and load during different races in youth and junior cyclists - Rodriguez-Marroyo, J. A.; Pernia, R.; Cejuela, R.; Garcia-Lopez, J.; Llopis, J.; Jose, G. (The Journal of Strength and Conditioning Research, 2011)
This study analyzed and compared the exercise intensity exerted by Youth and Junior cyclists in single-day and stage races. Heart rate was measured during the races and categorized according to 3 intensity zones: Z1 (below the ventilatory threshold [VT]), Z2 (between the VT and the respiratory compensation threshold [RCT]), and Z3 (above the RCT). The training impulse (TRIMP) was calculated by multiplying the sum of the time spent in each zone by 1, 2, and 3, respectively. Time spent in Z1, Z2, and daily TRIMP were significantly higher (p < 0.05) in Junior than in Youth in both single-day races (21.6 ± 1.9 min vs. 14.8 ± 1.6 min, 55.4 ± 2.3 min vs. 34.7 ± 1.9 min, and 257 ± 6 vs. 194 ± 6, respectively) and stage races (49.2 ± 3.4 min vs. 23.5 ± 4.7 min, 51.2 ± 2.6 min vs. 35.3 ± 3.7 min, and 201 ± 10 vs. 147 ± 7, respectively). In Youth and Junior, time and percentage time spent in Z3 and daily TRIMP were also significantly higher (p < 0.05) in single-day races (39.0 ± 1.9 min, 40.2± 1.9% and 225 ± 7) than in stage races (13.9 ± 1.8 min, 15.2 ± 1.8% and 174 ± 8). In conclusion, the present study showed that races in both Youth and Junior categories are highly demanding and that their intensity and exercise load are related to the total race duration.